Current status and strategic possibilities on potential use of combinational drug therapy against COVID-19 caused by SARS-CoV-2. Issue 17 (22nd November 2021) - Siddiqui, Arif Jamal; Jahan, Sadaf; Ashraf, Syed Amir; Alreshidi, Mousa; Ashraf, Mohammad Saquib; Patel, Mitesh; Snoussi, Mejdi; Singh, Ritu; Adnan, Mohd
Abstract: The spread of new coronavirus infection starting December 2019 as novel SARS-CoV-2, identified as the causing agent of COVID-19, has affected all over the world and been declared as pandemic. Approximately, more than 8, 807, 398 confirmed cases of COVID-19 infection and 464, 483 deaths have been reported globally till the end of 21 June 2020. Until now, there is no specific drug therapy or vaccine available for the treatment of COVID-19. However, some potential antimalarial drugs like hydroxychloroquine and azithromycin, antifilarial drug ivermectin and antiviral drugs have been tested by many research groups worldwide for their possible effect against the COVID-19. Hydroxychloroquine and ivermectin have been identified to act by creating the acidic condition in cells and inhibiting the importin (IMPα/β1) mediated viral import. There is a possibility that some other antimalarial drugs/antibiotics in combination with immunomodulators may help in combatting this pandemic disease. Therefore, this review focuses on the current use of various drugs as single agents (hydroxychloroquine, ivermectin, azithromycin, favipiravir, remdesivir, umifenovir, teicoplanin, nitazoxanide, doxycycline, and dexamethasone) or in combinations with immunomodulators additionally. Furthermore, possible mode of action, efficacy and current stage of clinical trials of various drug combinations against COVID-19 disease has also been discussed in detail. Communicated by Ramaswamy H. Sarma